Infrared spectroscopy : fundamentals and applications - Stuart, Barbara (Barbara H.) (Analytical techniques in the sciences., 2004)
Provides an introduction to those needing to use infrared spectroscopy for the first time, explaining the fundamental aspects of this technique, how to obtain a spectrum and how to analyse infrared data covering a wide range of applications. Includes instrumental and sampling techniques.